Respuesta :

-72/12=-6   Because 12×(-6)=-72

To find the answer, you'll have to do the inverse operation of what is shown. So in you're case, the inverse operation will be multiplication, since the original one is a division:

x / 12 = -6 → we take 12 to the right side of the equation

x = -6 * 12 → we do the I.O.* of "÷ 12" by solving -6 * 12

x = -72 → final answer



To prove your answer:

-72 / 12 = -6


Hope it helped,


BioTeacher101


(If you have any questions, feel free to ask them in the comments)

ACCESS MORE